Significance of Four Methionine Sulfoxide Reductases in Staphylococcus aureus - Singh, Vineet K. (Public Library of Science, 2015)

(untitled) (PLoS One)
Staphylococcus aureus is a major human pathogen and emergence of antibiotic resistance in clinical staphylococcal isolates raises concerns about our ability to control these infections. Cell wall-active antibiotics cause elevated synthesis of methionine sulfoxide reductases (Msrs: MsrA1 and MsrB) in S. aureus. MsrA and MsrB enzymes reduce S-epimers and R-epimers of methionine sulfoxide, respectively, that are generated under oxidative stress. In the S. aureus chromosome, there are three msrA genes (msrA1, msrA2 and msrA3) and one msrB gene. To understand the precise physiological roles of Msr proteins in S. aureus, mutations in msrA1, msrA2 and msrA3 and msrB genes were created by site-directed mutagenesis. These mutants were combined to create a triple msrA (msrA1, msrA2 and msrA3) and a quadruple msrAB (msrA1, msrA2, msrA3, msrB) mutant. These mutants were used to determine the roles of Msr proteins in staphylococcal growth, antibiotic resistance, adherence to human lung epithelial cells, pigment production, and survival in mice relative to the wild-type strains. MsrA1-deficient strains were sensitive to oxidative stress conditions, less pigmented and less adherent to human lung epithelial cells, and showed reduced survival in mouse tissues. In contrast, MsrB-deficient strains were resistant to oxidants and were highly pigmented. Lack of MsrA2 and MsrA3 caused no apparent growth defect in S. aureus. In complementation experiments with the triple and quadruple mutants, it was MsrA1 and not MsrB that was determined to be critical for adherence and phagocytic resistance of S. aureus. Overall, the data suggests that MsrA1 may be an important virulence factor and MsrB probably plays a balancing act to counter the effect of MsrA1 in S. aureus.